Pengaruh Non-Performing Loan (NPL) dan Loan to Deposit Ratio (LDR) terhadap Return on Asset (ROA) dengan Net Interest Margin (NIM) sebagai Variabel Mediasi pada Bank BUMN yang Terdaftar di BEI - Suci Susilawati; Nafisah Nurulrahmatiah (Jurnal Maksipreneur, 2021)
The financial performance of a bank can be measured through ROA. Bank Indonesia as a supervisory and supervisory institution prioritizes greater profitability, namely the Return on Asset (ROA) of a bank, so banks need to know what factors can affect the ROA of a bank. This study was conducted to analyze the effect of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return on Assets (ROA) with Net Interest Margin (NIM) as a mediating variable. The sample of this research consists of Bank Mandiri, Bank BNI, Bank BRI, and Bank BTN for the period 2015-2019. The research methods used include descriptive statistical analysis, outer model analysis, and inner model analysis. The results of this study indicate that NPL does not affect NIM, while LDR has a significant effect on NIM. Furthermore, NPL has a significant effect on ROA, while LDR does not affect ROA. This study also proves that NIM has a significant effect on ROA, but NIM does not mediate the effect of NPL on ROA, and NIM can mediate the effect of LDR on ROA.